2016
DOI: 10.1016/j.diabres.2016.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between daily and day-to-day glycemic variability and increased oxidative stress in type 2 diabetes

Abstract: Therefore, oxidative stress is associated with daily and day-to-day glucose variability in patients with T2DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 46 publications
3
67
0
2
Order By: Relevance
“…Therefore, in this study, when the HbA1c level reached about 7.5% (58 mmol/mol) after intervention, we gave interventions that targeted daily glucose variability and postprandial glucose. Because a strong association between glucose variability and oxidative stress is reported in crosssectional studies [8,9], improvement of glucose variability by treatment intervention was considered to result in reduction of oxidative stress. Several interventional studies of glucose variability on oxidative stress have been reported for patients with T2DM with an average HbA1c of approximately 7.5% (58 mmol/mol).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in this study, when the HbA1c level reached about 7.5% (58 mmol/mol) after intervention, we gave interventions that targeted daily glucose variability and postprandial glucose. Because a strong association between glucose variability and oxidative stress is reported in crosssectional studies [8,9], improvement of glucose variability by treatment intervention was considered to result in reduction of oxidative stress. Several interventional studies of glucose variability on oxidative stress have been reported for patients with T2DM with an average HbA1c of approximately 7.5% (58 mmol/mol).…”
Section: Discussionmentioning
confidence: 99%
“…A previous clinical study reported an association between oxidative stress and daily glucose variability [8]. Likewise, our group previously reported that oxidative stress was associated with both daily and dayto-day glucose variability [9]. On the other hand, studies with contradictory results have also been reported.…”
Section: Introductionmentioning
confidence: 88%
“…Also, expression of heat shock protein (HSP)72 and heme oxygenase (HO)-1, genes responsible for antioxidant defense mechanisms, is markedly lower in the skeletal muscle of T2D [54] (Table 1). In T2D, muscle expression of antioxidant genes further correlates with muscle oxidative capacity and insulin-stimulated glucose disposal [54, 55]. …”
Section: Links Between Oxidative Stress and Metabolic Diseasesmentioning
confidence: 99%
“…On the other hand, the positive correlation of ox-LDL and lipid peroxidation and the negative correlation of total antioxidant levels and SOD activity with insulin resistance were found to be independent of obesity in one study [47]. In T2D, muscle expression of antioxidant genes further correlates with muscle oxidative capacity and insulin-stimulated glucose disposal [54, 55]. Finally, oxidative stress is further associated with daily and day-to-day glucose variability [54, 55].…”
Section: Links Between Oxidative Stress and Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation